Rinitis Alergi: Patofisiologi, Diagnosis, dan Strategi Penanganan Terkini - Muhammad Rizky Simanjuntak (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Allergic rhinitis (AR) is a chronic inflammatory disorder of the nasal mucosa mediated by immunoglobulin E (IgE) in response to allergen exposure. This condition has become a significant global health concern because of its increasing prevalence and substantial impact on quality of life, sleep, cognitive function, and work productivity. AR is also commonly associated with other atopic diseases, including asthma and atopic dermatitis. This article aims to review the current understanding of allergic rhinitis, focusing on epidemiology, pathophysiology, clinical manifestations, diagnostic approaches, and evidence-based management strategies. This study used a narrative literature review method by analyzing scientific articles, clinical guidelines, and peer-reviewed journals published between 2015 and 2025. Literature sources were obtained from PubMed, Google Scholar, and relevant medical databases using keywords related to allergic rhinitis, IgE, diagnosis, and immunotherapy. The findings indicate that allergic rhinitis involves complex immune mechanisms characterized by Th2 lymphocyte activation, IgE production, and inflammatory mediator release. Diagnosis is primarily established clinically and supported by allergy testing such as skin prick tests or serum-specific IgE measurement. Intranasal corticosteroids remain the first-line therapy for moderate to severe cases, while antihistamines and leukotriene receptor antagonists are used as adjunctive therapies. Allergen immunotherapy has shown effectiveness in modifying disease progression and improving long-term outcomes. In conclusion, allergic rhinitis is a manageable chronic disease that requires a comprehensive and individualized treatment approach involving environmental control, pharmacotherapy, and immunotherapy.